Navigated versus conventional transfixation of AC joint injuries: Feasibility and accuracy. (May 2013) - Stübig, Timo; Jähnisch, Torsten; Petri, Maximilian; Hawi, Nael; Zeckey, Christian; Krettek, Christian; Citak, Musa; Meller, Rupert
<x xml:space="preserve">Abstract</x> Objective: Transfixation of the acromioclavicular (AC) joint is a well-established technique for treating Rockwood IV to VI lesions. However, several complications, including pin breakage or pin migration due to incorrect placement, have been reported in the literature. A cadaveric study was performed to investigate whether the use of 3D navigation might improve the accuracy of AC joint transfixation. Methods: Seventeen transfixations of the AC joint (8 non-navigated, 9 navigated) were performed minimally invasively in cadaveric shoulders. For the navigated procedures, a 3D C-arm (Ziehm Vision FD Vario 3D) and a navigation system (BrainLab VectorVision) were used. Reference markers were attached to the spina scapulae, then a 3D scan was performed and the data transferred to the navigation system. Two Kirschner wires (K-wires) were placed either freehand under fluoroscopic control (in the non-navigated group) or with the use of a navigated drill guide. Radiological analysis was performed with OsiriX software, measuring the distance of the K-wires from the center of the AC joint. For statistical analysis, Student's t-test was performed, with the significance level being set to p < 0.05. Results: The maximum distance of the K-wires from the center of the AC joint was 5.4 ± 1.1 mm for the freehand non-navigated group and 3.1 ± 1.6 mm for the navigated group (p = 0.0054). The minimum distance of the K-wires from the AC joint center was 3.0 ± 0.6 mm for the freehand group and 1.6 ± 0.6 mm for the navigated group (p = 0.0002). The radiation time was significant lower for the freehand group (41.25 ± 20.4 seconds versus 79.5 ± 13.3 seconds for the navigated group, p = 0.004). There was no statistical difference between the groups with respect to the time required for surgery (11.25 ± 3.6 min for the freehand group and 12.6 ± 4.6 min for the navigated group; p = 0.475). In the freehand group, the AC joint was penetrated by both K-wires in 87.5% of the procedures, compared to 100% in the navigated group. Both K-wires were placed completely intraosseously in the clavicula in 50% of the procedures in the freehand group, compared to 88% in the navigated group. Conclusion: Three-dimensional navigation may improve the accuracy of AC joint transfixation techniques. However, the radiation time is increased when using the navigated procedure, while the overall operation time remains comparable. Nevertheless, a 3D C-arm with a variable isocentric design is recommended for the acquisition of the shoulder scans.